149k views
3 votes
F(n) = f(n – 1) + f(n – 2); f(1) = 2; f(2) = 1.

Describe in words the relationship between the terms created by this algebraic rule.

User Dolphin
by
4.4k points

1 Answer

2 votes

f(n) is the nth term

Each term f(n) is found by adding the terms just prior to the nth term. Those two terms added are f(n-1) and f(n-2)

The term just before nth term is f(n-1)

The term just before the (n-1)st term is f(n-2)

----------------

For example, let's say n = 3 indicating the 3rd term

n-1 = 3-1 = 2

n-2 = 3-2 = 1

So f(n) = f(n-1) + f(n-2) turns into f(3) = f(2) + f(1). We find the third term by adding the two terms just before it.

f3) = third term

f(2) = second term

f(1) = first term

User Hatem Jaber
by
4.5k points